Environmental consequences of agro - pesticides necessary for rural development - Hussein, Mohd Yusof (1985)
The Malaysian government's strategy for economic development is sustaining rapid industrial growth and focussing its development programmes on the rural population in an all out effort to redress rural poverty. The rural poverty level, inspite of expected rapid development, is forcasted to be still around 50% by 1990. The rural scenario in Malaysia is no different. Agriculture is still dominated by the small farmers of the rural areas which remain as a dominant poverty trap. The idealized transition of agriculture into a modern sector, developed and reorganized into efficient industry supplying the food requirements of the country is yet to materialize. It is, thus, not suprising for agricultural development (synonymous to rural development) to have received top priority. The poor farmers of the rural sector are yet to benefit much from modern agriculture which certainly needs the essential modern inputs and technology. One of the modern tools of agricultural modernization is chemical pesticides (agro-pesticides). Agro-pesticides remains, inspite of their adverse publicity, our most powerful tool in the management of crop pests which are still causing heavy crop losses annually. Are agropesticides really necessary? This will be one of questions that will be answered in this paper. The paper will largely examine in some details the Malaysian version of the environmental consequences resulted from the long usage and overreliance upon toxic agropesticides relative to environmental pollution, ecological imbalances and disruptions~ problems of pesticide-resistance pests added to the environment~ recurrent pest and disease outbreaks~ adverse effects on human health and future generations and finally the exclusion of traditional pest control technologies. Results of a recent survey on small farmers to understand their perception of the impact of agropesticides on the environment and their confidence on non-chemical method to control pests are presented. The paper finally discussed an appropriate immediate measures to be taken and our future strategies in protecting the rural environment.